Development of a web-based information system for monitoring of hemodialysis adequacy - Mohamad Jebraeily; Reza Safdari; Bahlol Rahimi; Khadijeh Makhdoomi; Marjan Ghazisaeedi (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: Given the significant impact of dialysis adequacy on the quality of life and survival of hemodialysis patients, an information system for assessment of the treatment plan is necessary. Objectives: In this study, a web-based information system was developed to monitor hemodialysis adequacy in hemodialysis center of Taleghani hospital of Urmia. Patients and Methods: The study is organized into four phases; determination of minimum data set, designing an information system for monitoring the dialysis adequacy, implementing in a hospital setting and finally impact of the information system on dialysis adequacy. Results: This system designed in ASP.NET platform and C# programming language and SQL, server database was applied for managing the data. This system implemented in server of hemodialysis center of the hospital. The results of statistical analysis showed that information system on the hemodialysis adequacy indicators has a significant effect (P<0.05). Conclusion: We found that the designed information system is capable of promoting hemodialysis adequacy.